Measuring Diet Quality Across the Lifespan: Introducing the New Healthy Eating Index-Toddlers-2020 and Healthy Eating Index-2020. (14th June 2022) - Reedy, Jill; Lerman, Jennifer; Herrick, Kirsten; Shams-White, Marissa; Zimmer, Meghan; Mathieu, Kevin Meyers; Dodd, Kevin; Kahle, Lisa; Stoody, Eve; Pannucci, TusaRebecca
Abstract: Objectives: Researchers at the National Cancer Institute (NCI) and the U.S. Department of Agriculture (USDA) collaborated to update the Healthy Eating Index (HEI) based on the 2020–2025 Dietary Guidelines for Americans (DGA). Methods: The USDA's Dietary Patterns serve as the foundation for the HEI and provide standards to assess alignment with the DGA. Given that these dietary patterns for Americans 2 years and older remained virtually unchanged from the 2015–2020 DGA and there were no major changes in key recommendations, the components and scoring for HEI-2020 align fully with HEI-2015. However, guidance and distinct dietary patterns were introduced for toddlers ages 12–23 months (700–1, 000 calories). Thus, a new index, HEI-Toddlers-2020, was developed and evaluated. Sensitivity analyses examined standards based on key recommendations rather than dietary patterns for Added Sugars and Sodium, compared the two sets of 1, 000 calorie standards for Whole Grains and Refined Grains, and evaluated varying considerations with fat-specific constructs, as Saturated Fat is not restricted for children under 2 years. Results: The 13 components for HEI-Toddlers-2020 are the same as those in HEI-2020. However, the standards and scoring approach for HEI-Toddlers-2020 have key differences and highlight the focused guidance for this age group. The standards for all maximum scores—except Added Sugars and Sodium—are based on the least-restrictive profiles from the dietary patterns (Added Sugars and Sodium draw on the key recommendations). The standards for minimum scores for Total Fruit, Whole Fruit, Total Vegetables, Greens and Beans, Whole Grains, Dairy, Total Protein Foods, and Seafood and Plant Proteins are zero; for other components—Fatty Acids, Refined Grains, Sodium, Added Sugars, and Saturated Fats—standards are set at the 15 th (Fatty Acids) or 85 th (all others) percentiles of 1-day intake distributions from the 2007–2018 National Health and Nutrition Examination Survey. Conclusions: The new HEI-Toddlers-2020 and updated HEI-2020 can be used to assess diet quality beginning at age 12 months. The consistency in component approach enables optimal bridging, and further research will inform how the indices can be used in conjunction to assess diet quality across the lifespan. Funding Sources: None.